Analisis faktor-faktor yang mempengaruhi pilihan karir mahasiswa farmasi di Universitas Andalas - Erniza Pratiwi; Deddi Prima Putra; Laura Syahrul (Universitas Ahmad Dahlan, 2017)
Based on PP 51 of the year 2009, the pharmaceutical practices have very of choice of carreer-field. The purpose of this research is to determine the most important factor that influence the career choices and the carrier priority choosing of pharmacy students. It was a descriptive study which conducted by survey method by using stratified random sampling. The respondents are 85 students, consisting of 1st, 2nd, 3rd and 4th grade students from Faculty of Pharmacy, Andalas University. The results shown that, in term of the profile of respondent, known that the most of the students choices to work at Pharmaceutical Industry, Hospital, University/Research Institute, pharmacy, pharmacy retail and others career-field (such as BPOM, civil servant at ministry of health and enterpreneur) of 48.2%, 35.3 %, 4.7%, 3.5 % 2.4 % and 5.9%, respectively. Based on the descriptive analysis, it was described that work field was the most important criteria in choosing their future career. The others important criterias those also afforded as the affecting factors were geographis, payment/income, flexibility of work-schedule, possibility of career-development and benefit, successively. The results showed that the independent sample t-test in term of gender (i.e. men and women) showed the same three main affecting factors for choosing the career-field (including field of work, geographis as well as payment/income). However, 4th, 5th and 6th factors were showed the different results. In this researh, the work field is the most important for the respondents to decide their future choice and the carrier priority choosing from the respondents is to work in the Pharmaceutical Industry.